Deliberate birth spacing in nineteenth century northern Sweden - Kolk, Martin (European Journal of Population / Revue européenne de Démographie, 2012)
Fertility in nineteenth century Europe before the fertility transition has been described as high, unregulated, and stable; the extent of fertility control remains a controversial topic. The aim of this study is to determine whether there is evidence of deliberate birth spacing in northern Sweden prior to the onset of the fertility transition. This study analyses micro-level parish records of 9,636 women in nineteenth century northern Sweden—a remote but, at the time, economically dynamic frontier region of Sweden. Event history analysis reveals evidence of birth spacing that suggests some conscious birth control. Piecewise exponential models of the transition from second to third birth reveal circumstances in which parents increased or decreased the time to next birth. The results on the survival of previous children, geographic context, sex of previous children, and variations in grain prices all indicate that parents deliberately manipulated the spacing between births. [author's abstract] Si la fécondité prétransitionnelle en Europe au 19e siècle a été décrite comme élevée, stable et non régulée, l'existence d’un certain contrôle de la fécondité reste un sujet controversé. L'objectif de cet article est de déterminer l'éventuelle existence d'un espacement volontaire des naissances dans le Nord de la Suède avant le début de la transition de fécondité. Les données proviennent des registres paroissiaux et concernent 9 636 femmes du Nord de la Suède au 19e siècle, dans une région éloignée mais frontalière caractérisée par un grand dynamisme économique à cette époque. L'analyse biographique révèle un espacement des naissances qui suggère un certain contrôle volontaire des naissances. Des modèles exponentiels par morceaux de la transition entre la deuxième et la troisième naissance révèlent des situations au cours desquelles les parents allongent ou raccourcissent l'intervalle entre naissances. Les résultats basés sur la survie de l'enfant précédent, le contexte géographique, la composition par sexe de la fratrie ...